Progress and Perspectives of Conducting Metal–Organic Frameworks for Electrochemical Energy Storage and Conversion - Minggui Li; Guangxun Zhang; Yuxin Shi; Huijie Zhou; Yongcai Zhang; Huan Pang (Chemistry, 2023)
The metal–organic framework (MOF) is a kind of porous material with lattice materials. Due to its large surface area and structural diversity, it has made great progress in the fields of batteries, capacitors, electrocatalysis, etc. Conductive MOF (c-MOF) increases the conductivity based on the original advantages of the MOF, which is more suitable for the development of batteries, capacitors, electrocatalysis, and other fields. This review summarizes the preparation of c-MOF and the research progress of conductive MOFs in the field of electrochemical energy storage and conversion.